PBL as a New Pedagogical Approach for Translator Education - Inoue, Izumi (Meta, 2005)
AbstractIt appears that current mainstream translator education is dominated by what Kiraly (2000) calls a “transmissionist approach’. This approach is of limited benefit when the novices must apply what they have learnt to real situations that they will encounter as professionals. Thus, it can be said that we are at the point where we need to seek a new approach in which we can help novices to develop their own competence.Problem-Based Learning (PBL) is aimed at promoting novices’ autonomy and self-reflective actions which are required in a professional practice when they face problems and challenging situations. While PBL is now commonly employed in such areas, there has as yet been no significant movement to introduce this approach in the area of translator education.This paper consists of three major components. First of all, the problems of educator-centred teaching in translation will be discussed. This will be followed by an outline of the benefits of PBL for translator education, from both theoretical and practical perspectives. The feasibility of PBL as an effective model for translator education will be then considered based on empirical case studies.